Genome-wide Association Study Identifies New Loci for Resistance to Leptosphaeria maculans in Canola - Raman, Harsh; Raman, Rosy; Coombes, Neil; Song, Jie; Diffey, Simon; Kilian, Andrzej; Lindbeck, Kurt; Barbulescu, Denise M.; Batley, Jacqueline; Edwards, David; Salisbury, Phil A.; Marcroft, Steve (Frontiers in Plant Science, 2016)
Blackleg, caused by Leptosphaeria maculans, is a significant disease which affects the sustainable production of canola. This study reports a genome-wide association study based on 18,804 polymorphic SNPs to identify loci associated with qualitative and quantitative resistance to L. maculans. Genomic regions delimited with 503 significant SNP markers, that are associated with resistance evaluated using 12 single spore isolates and pathotypes from four canola stubble were identified. Several significant associations were detected at known disease resistance loci including in the vicinity of recently cloned Rlm2/LepR3 genes, and at new loci on chromosomes A01/C01, A02/C02, A03/C03, A05/C05, A06, A08, and A09. In addition, we validated statistically significant associations on A01, A07 and A10 in four genetic mapping populations, demonstrating that GWAS marker loci are indeed associated with resistance to L. maculans. One of the novel loci identified for the first time, Rlm12, conveys adult plant resistance and mapped within 13.2 kb from Arabidopsis R gene of TIR-NBS class. We showed that resistance loci are located in the vicinity of R genes of A. thaliana and B. napus on the sequenced genome of B. napus cv. Darmor-bzh. Significantly associated SNP markers provide a valuable tool to enrich germplasm for favorable alleles in order to improve the level of resistance to L. maculans in canola.